Bhutan : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Bhutan has evolved from a closed economy to a trading nation that exhibits a high degree of dependence on trade. Exports have grown rapidly but overall the country's trade deficit continues to widen owing to an even faster growth in the value of imports. The manufacturing and industry sector is constrained by various factors that impede its further development. FDI and joint ventures are some of the mechanisms that must be actively promoted to help jump start the process.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet